Pengaplikasian Filipi 4:6-8 dalam Cognitive Behavioral Therapy terhadap Dewasa Muda - Putri Dyna Barimbing; Grace A Ticoalu-Thenu (Voice, 2023)
Society translates health as physical health, while humans consist of body, soul, and spirit. The health of the body cannot be separated from the health of the soul and the health of the spirit. God created humans very well, but with the ability to sin, humans sinned and the curse entered the world. Having fallen into sin, humans as the image and likeness of God must try to change their core beliefs that have been influenced by the four lies of the devil. With the divine authority of God's word using one of the psychotherapy techniques of Cognitive Behavioral Therapy, Christians are expected to experience a change in core beliefs. This change occurs due to changed behavior after renewing the mind in accordance with Philippians 4: 6-8. Qualitative research was conducted by way of exposition of Philippians 4:6-8. The research also took literature and included daily notes from anxiety disorder patients. It is hoped that early adult Christian anxiety patients will understand that the Bible is sufficient to answer the problems they face and be able to make peace with the disease of anxiety disorder and function again in the broader community.